2004
DOI: 10.3346/jkms.2004.19.4.624
|View full text |Cite
|
Sign up to set email alerts
|

Transient Paraparesis After Laminectomy in a Patient with Multi-Level Ossification of the Spinal Ligament

Abstract: Acute neurologic deterioration is not a rare event in the surgical decompression for thoracic spinal stenosis. We report a case of transient paraparesis after decompressive laminectomy in a 50-yr-old male patient with multi-level thoracic ossification of the ligamentum flavum and cervical ossification of the posterior longitudinal ligament. Decompressive laminectomy from T9 to T11 was performed without gross neurological improvement. Two weeks after the first operation, laminoplasty from C4 to C6 and additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…There are several theories for neurological deterioration subsequent to cord decompression, and iatrogenic cord insult is a well-known possible etiology (11,12). However, the timing, nature and underlying circumstances of the neurological deficits observed in the present patients suggests that alternative underlying mechanisms more likely than direct cord trauma (4)(5)(6)8). Post-operative hematomas may be a cause of neurological deterioration (13), but the patients are able to move all extremities following the surgical procedure (5,(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several theories for neurological deterioration subsequent to cord decompression, and iatrogenic cord insult is a well-known possible etiology (11,12). However, the timing, nature and underlying circumstances of the neurological deficits observed in the present patients suggests that alternative underlying mechanisms more likely than direct cord trauma (4)(5)(6)8). Post-operative hematomas may be a cause of neurological deterioration (13), but the patients are able to move all extremities following the surgical procedure (5,(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…However, careful surgical techniques and intraoperative neuromonitoring can indicate any potential trauma to neural tissue during the tumor removal and decompression procedures (1,4,5). In the absence of clear etiology, vascular insult and toxic mechanisms may be responsible for the neurological deterioration (4,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a potential mechanism for decompression-related reperfusion injury of chronic ischemia (stenosis) has to date not been established. Microthrombi compromising the watershed regions of arterial supply are another possible etiology of transient postoperative paralysis after thoracic decompression surgery [8]. Compromise of the watershed region of the spine deserves special consideration in the presented cases, as surgeries were performed at a watershed zone, supplied by the artery of Adamkiewicz, which usually arises on the left at the T8-L2 level [11] and at T9 or T10 in 50 % of patients [1].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously suggested that decompression of a previously severely compressed region of the spinal cord may lead to sensory or motor deficits during the early postoperative period [4,8], and reperfusion injury as a mechanism contributing to neural damage has been described in the setting of acute ischemic events [2,6], however, not for chronic conditions such as thoracic stenosis.…”
Section: Introductionmentioning
confidence: 99%